Observations and Reflections from Sub-Saharan Africa. Comment on Shahait, M. Urology Practice in Low- to Middle-Income Countries. Soc. Int. Urol. J. 2024, 5, 374–375 - Saleh A. Nedjim; Kaleab H. Gebreselassie; Mahamat A. Mahamat; Ouima J. D. Ziba; Anteneh T. Kifle; Abdullahi Khalid; Rimtebaye Kimassoum; Choua Ouchemi; Alain Khassim Ndoye (Société Internationale d’Urologie Journal)
Shahait’s article on “Urology Practice in Low- to Middle-Income Countries” [...]